Phytochemical composition, antioxidant and in vivo antidiabetic activities of the hydroethanolic extract of Eugenia florida DC. (Myrtaceae) leaves - Bastos, R. G.; Salles, B. C. C.; Bini, I. F.; Castaldini, L. P.; Silva, L. C. D.; Vilela, A. A.; Micheloni, A. L. C.; Silva, G. M. da; Silva, P. H. C. da; Maure, A. K.; Santos, L. L.; Rosa, C. P.; et al. (Elsevier B.V., 2019)
Some literature studies have shown the popular use of species of Eugenia sp. leaves as an antioxidant, hypoglycemic, hypotensive and antipyretic. However, the species E. florida DC. shows few studies in this field of knowledge. In this way, it becomes a choice for further research. Several chemical compounds, such as phenolic acids, flavonoids, saponins and tannins, have previously been identified in the species and may be related to biological activity. The aim of present work was done to identify the chemical compounds present in the hydroethanolic extract of Eugenia florida DC. leaves by high-performance liquid chromatography coupled to mass spectrometry, as well as to investigate the antioxidant and antidiabetic effects in alloxan-induced type 1 diabetic rats. Initially, the data collection, specimen deposition of leaves of E. florida DC. and the preparation of the hydroethanolic extract were done. The chemical characterization of the major compounds in the extract was done using a liquid chromatograph coupled to the mass spectrometer, in the negative ionization mode. The evaluation of the antioxidant activity of the extracts was done by the DPPH method. To evaluate the biochemical parameters in the Wistar diabetic rats, alloxan was administered at a dose of 140 mg/kg to the diabetic groups, and the extract was diluted in water to 200 mg/mL and administered to all groups for 30 days. After this period, whole blood from the animals was collected for the determination of some biochemical parameters, as well as livers and kidneys for the evaluation of the effects of the extract on the control of lipid peroxidation. The phytochemical analysis of the extract revealed the presence of substances belonging to the classes described in the literature for the genus Eugenia sp., such as flavonoids, tannins and phenolic acids, based on the molecular mass and the fragmentation patterns obtained. The leaf extract presented potential DPPH radical scavenging activity very close to the catechin standard. In the evaluation of the biochemical parameters of diabetic rats treated with the extract, significant decreases in serum levels of glucose, fructosamine and triglycerides (38.0%, 31.0% and 19.7%, respectively) were observed, as well as an increase in HDL cholesterol (10.3%). The administration of the extract had no significant effect on renal function, AST and ALT activity and on the other parameters of the lipid profile. In addition, there was improvement in liver and kidney damage in treated diabetic animals, through reduction of MDA values in livers and kidneys (17.3% and 13.8%, respectively). Thus, the species E. florida DC. presents an interesting biological potential, due mainly to its bioactive secondary metabolites, which showed promising antioxidant activity and biochemical parameters in diabetic rat models. (C) 2019 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Eugenia florida; Chemical characterization; Antioxidant activity; Mass spectrometry; Biochemical parameters; Diabetic rats